Estudio del uso de aplicaciones interactivas en dispositivos móviles para el proceso de enseñanza aprendizaje de matemática en el Instituto Tecnológico Babahoyo de la ciudad de Babahoyo. - Caicedo Franco, Edgar Vladimir (2020)
Today more than ever it is important to think about what is the appropriate use to be made of technologies in teaching processes. That is why incorporating technology into education brings a series of benefits that help improve efficiency and productivity in the classroom, as well as increase the interest of children and adolescents in academic activities. The Internet and access to increasingly intuitive mobile devices has put a paradigm shift in the use of technology. This change is also evident in the field of education, in which more and more things can be done, taking advantage of the network and its possibilities, both in and outside the classroom. However, now with the Internet and mobile technology to the fullest, even more technological elements are incorporated into the educational environment. Interactive whiteboards, virtual classrooms, and endless electronic resources to conduct research or do schoolwork are some of the ways in which digital technology has integrated with educational establishments.